Staff Retention in Nepalese ‘A’ Class Banking Institutions in Surkhet Valley, Nepal - Rijal, Rheet; Danuwar, Ranjana Kumari; KC, Harendra; Yogi, Sanjaya (Journal of Business and Social Sciences Research, 2025)
Employee retention is a significant concern for organisations, especially in competitive sectors like banking, where skilled employees are essential for operational efficiency and customer satisfaction. High turnover creates financial costs, reduces productivity, and disrupts customer service. This study analyses examines key factors influencing employee retention in Nepalese Class “A” banking institutions in Surkhet Valley. It specifically analyses the effects of the working environment, training and development, salary and benefits, supervisor–subordinate relationships, and job security. A quantitative causal-comparative design was adopted, and primary data were collected through a structured questionnaire from 155 bank employees. Based on the descriptive and inferential analyses the findings show that a positive working environment significantly enhances retention, while training and development improve career growth and commitment. Competitive salary and benefits strongly motivate employees to remain in their jobs. Supportive supervisor–subordinate relationships foster loyalty, and job security remains a crucial determinant of retention. Overall, the study highlights that improving workplace conditions, investing in employee development, ensuring fair compensation, and strengthening leadership are essential for reducing turnover and promoting workforce stability in the banking sector.